2017
DOI: 10.1038/onc.2017.211
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide loss-of-function genetic screening identifies opioid receptor μ1 as a key regulator of L-asparaginase resistance in pediatric acute lymphoblastic leukemia

Abstract: L-asparaginase is a critical chemotherapeutic agent for acute lymphoblastic leukemia (ALL). It hydrolyzes plasma asparagine into aspartate and NH3, causing asparagine deficit and inhibition of protein synthesis and eventually, leukemic cell death. However, patient relapse often occurs due to development of resistance. The molecular mechanism by which ALL cells acquire resistance to L-asparaginase is unknown. Therefore, we sought to identify genes that are involved in L-asparaginase resistance in primary leukem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 13 publications
0
44
1
Order By: Relevance
“…Whereas in various cancer types, OPRM1 expression has been associated with higher staging and/or poor outcome, our findings suggest this is not the case in melanoma. As to the effects of Met, Friesen et al had reported that apoptosis rates increased by about 50% in leukaemia and glioblastoma cell lines treated with Met combined with chemotherapeutic agents.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…Whereas in various cancer types, OPRM1 expression has been associated with higher staging and/or poor outcome, our findings suggest this is not the case in melanoma. As to the effects of Met, Friesen et al had reported that apoptosis rates increased by about 50% in leukaemia and glioblastoma cell lines treated with Met combined with chemotherapeutic agents.…”
Section: Discussioncontrasting
confidence: 70%
“…Based on a series of studies suggesting a role of Met as a chemotherapy sensitizer in certain cancer types, we addressed the potential/validity of this hypothesis in the setting of melanoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The postulated ability of methadone to enhance cancer therapy [ 16 , 17 , 18 ] has received considerable attention in recent years, but remains highly controversial. Preclinical evidence for a tumoricidal methadone effect has been obtained in vitro and in mouse models for various tumor identities, such as leukemia [ 17 , 18 , 78 , 79 , 80 ], glioblastoma [ 16 , 81 , 82 ], neuroblastoma [ 83 ], and carcinoma cells [ 13 , 14 , 83 , 84 , 85 , 86 ]. These studies are summarized in Table 3 .…”
Section: Evidence For a Tumoricidal Activity Of Methadonementioning
confidence: 99%
“…Besides high expression and activity of ASN, host factors, especially ASNase antibody production, were also reported to be associated with the drug resistance of ASNase. However, it has been reported that the host factors would eventually result in high expression and activity of ASN [10,13,14]. erefore, to guide the decision of switching preparations or dose escalation of ASNase, the monitoring of drug concentration or therapeutic markers were necessary for ALL patients.…”
Section: Introductionmentioning
confidence: 99%